Reading Hadrah Basaudan: Study of living Qur'an at Hidayatus Salikin Boarding School Pembuang Hulu Village - Maulidah, Afuwah Nur; Erawati, Desi; Munirah, Munirah (LP2M UIN KH.Achmad Siddiq Jember, 2023)
This study discusses the phenomenon of reading Hadrah Basaudan as a solution in society, which currently has a low level of awareness of the importance of grounding the Qur'an in people's daily lives. There are two objectives in this study: to dig into the implementation and meaning of the Hadrah Basaudan tradition and see female students’ perception toward the recitation of Hadrah Basaudan. This field research used a qualitative descriptive method that systematically describes facts and factual data. The primary data sources used are the results of interviews and surveys of Hadrah Basaudan reading activities conducted by female students of the Hidayatus Salikin Islamic boarding school and analyzed in the frame of related literature review and also used cultural society paradigm theory by Emile Durkheim with functional reception by Ahmad Rafiq. The result showed that: 1) Practice of Hadrah Basaudan recitation done with routine and contained recitation that meant as praise to Prophet Muhammad along with interaction on Al-Qur’an verses which were Al-Fatihah, Yaasin, and Al-Anbiya Verse 101-112 that had meaning as a medium to bring nearer with Allah, prophet Muhammad, and noble characters in Hadrah Basaudan. 2) Students’ perception of Hadrah Basaudan was a purifying process to Allah, facilitating the reading of the Al-Qur’an, self-protection, antidote to disaster, heart care, wish fulfillment, ease of affairs, and self-reminders.